Ransomware as a security threat – social and criminal legislation aspects - Putnik, Nenad; Milošević, Mladen; Cvetković, Vladimir (Sociološki pregled, 2022)
This article focuses on the analysis of social and criminal aspects of the phenomenon of ransomware-malware abuse. The authors’ basic hypothesis is that the optimal mechanisms in terms of security and Criminal Code protection against this specific form of attacks on computer systems and data stored therein are still underdeveloped.The review of scientific and professional literature and the use of legal-dogmatic and normative methods by various authors have shown that crime related to the use of ransomware- malware has a potential to seriously endanger certain segments of modern society - economy, sensitive personal data, national and supranational critical infrastructure. The authors have also noted the shortcomings of currently available legal solutions.The authors conclude that it is necessary to conduct tailored educations of computer system users and also to undertake appropriate activities for the purpose of improving security culture. The authors additionally present concrete proposals for improving the legal framework for criminal legislation.
Keywords: ransomware-malware; social aspects of ransomware-malware attacks; Criminal Code protection against cybercrime; critical infrastructure